Dopamine partial agonist actions of the glutamate receptor agonists LY 354,740 and LY 379,268 - Seeman, Philip (2008)
Because glutamate compounds alter the release of dopamine and prolactin, the present study examined whether group II metabotropic receptor agonists, LY 354,740 and LY 379,268, had any direct in vitro action on dopamine D2 receptors on rat striatal tissue, cloned D2Long receptors, and prolactin release from anterior pituitary cells. In competition versus the D2-specific ligand [(3)H]domperidone, LY 354,740 had a dissociation constant of 24 nM at D2(High) (the functional high-affinity state of dopamine D2 receptors), while the value for LY 379,268 was 21 nM. LY 354,740 also stimulated by 50% the incorporation of [(35)S]-GTP-gamma-S at a concentration of 120 nM, but its maximal stimulation was only 22% of the maximum elicited by dopamine. LY 379,268 stimulated by 50% the incorporation of [(35)S]-GTP-gamma-S at 280 nM, but its maximal stimulation was also only 22% of the maximum elicited by dopamine. However, both LY 354,740 and LY 379,268 potently inhibited the dopamine-induced incorporation of [(35)S]-GTP-gamma-S with inhibitory Ki values of 43 nM and 30 nM, respectively. The release of prolactin from rat isolated anterior pituitary cells in culture was 50% inhibited by 20 nM LY 379,268 and by 100 nM LY 354,740. These Ki values are similar to those known for the mGluR II receptor, suggesting that these compounds may have both glutamate and dopamine actions in vivo. The dopamine agonist and antagonist actions of these compounds indicate that these drugs have properties of a dopamine partial agonist, and may, therefore, have antipsychotic action.